COMPARATIVE EVALUATION OF NOVEL LOW-COST MOISTURE METERS SUITABLE FOR GRAIN MOISTURE MEASUREMENT (2013)
Monitoring grain quality is an importa. * postharvest activity which starts at harvest, continuing during stcage and up to the point of sale. High moisture in stored maize can be detrimental to food safety because of the likelihood of aflatoxin contamination and other forms of deterioration. Moisture meters are devices which provide real-time access to measuring moisture levels thereby allowing farmers .' m eet grain quality requirements. A newly developed low- co ^ moisture meter known as the Post-Harvest Loss (PHL) moisture meter is a device with potentials for massive deployment among smallholder farmers. This study was therefore set up to compare the efficiencies of some existing moisture meters co m’ ared with this newly developed device. Two commercially available moisture meters — Dickey john GAC 2100 and John Deere me ters were compared with the PHL moisture meter and oven- dried method (ASABE standards) used as control. Maize grains from a bagged storage experiment were used as samples over a 12- month period. Results showed that the moisture meters had a positive difference of <3% MCwb relative to oven-dried method. Average measurements showed variances of 2.34, 1.08 and 0.56% MCwb for John Deere, PHL and GAC 2100 meters respectively, when compared with the oven-dried method. Thus, it was concluded that the low cost PHL moisture meter may serve as an effective alternative to the more expensive types and may be relatively easy to adopt for laboratory and field use among smallholder farmers in sub-Saharan Africa.